Interseismic Coupling‐Based Earthquake and Tsunami Scenarios for the Nankai Trough. Issue 7 (6th April 2018) - Baranes, H.; Woodruff, J. D.; Loveless, J. P.; Hyodo, M.
Abstract: Theoretical modeling and investigations of recent subduction zone earthquakes show that geodetic estimates of interseismic coupling and the spatial distribution of coseismic rupture are correlated. However, the utility of contemporary coupling in guiding construction of rupture scenarios has not been evaluated on the world's most hazardous faults. Here we demonstrate methods for scaling coupling to slip to create rupture models for southwestern Japan's Nankai Trough. Results show that coupling‐based models produce distributions of ground surface deformation and tsunami inundation that are similar to historical and geologic records of the largest known Nankai earthquake in CE 1707 and to an independent, quasi‐dynamic rupture model. Notably, these models and records all support focused subsidence around western Shikoku that makes the region particularly vulnerable to flooding. Results imply that contemporary coupling mirrors the slip distribution of a full‐margin, 1707‐type rupture, and Global Positioning System measurements of surface motion are connected with the trough's physical characteristics. Plain Language Summary: In regions that are vulnerable to earthquakes, constructing rupture scenarios based on scientific observations of faults is key to managing risk. High‐precision Global Positioning System measurements that track the motion of Earth's crust can be used to estimate interseismic coupling, which is a measure of frictional locking along fault interfaces that causes stress buildup between earthquakes. Past studies have shown that the distribution of coupling preceding an earthquake is correlated with rupture during an earthquake. We demonstrate methods for constructing rupture scenarios based on estimates of coupling for southwestern Japan's Nankai Trough, where a magnitude 8–9 earthquake is likely to occur within the next few decades. Modeled ground surface deformation and tsunami inundation for these coupling‐based rupture scenarios are similar to historical and geologic records of the largest known Nankai earthquake in CE 1707 and to an independent rupture model based on the trough's physical characteristics. Notably, these models and records all show that the ground surface around western Shikoku sinks during earthquake rupture and becomes particularly vulnerable to tsunami flooding. Our results imply that contemporary coupling mirrors the rupture pattern of the Nankai Trough's largest known historical event and that Global Positioning System measurements of surface motion are connected with the trough's physical characteristics. Key Points: Methods are demonstrated for constructing earthquake rupture scenarios based on the scaling of interseismic coupling to coseismic slip The resulting ground deformation and tsunami are similar to the largest known Nankai earthquake and an independent quasi‐dynamic model Results show coupling mirrors slip for a full‐margin rupture and provide evidence for a region of focused subsidence in western Shikoku